The Role of Total Quality Management in Enhancing Employees’ Performance Efficiency: A Field Study at the Al-Alawi Complex of the Imam Ali Holy Shrine - جودة زكريا فاضل; جودة منتظر فاضل (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study aims to explore the role of Total Quality Management (TQM) in enhancing the efficiency of employee performance within organizations. It investigates the relationship between the core principles of TQM—such as continuous improvement, participation in decision-making, and performance evaluation—and the level of employee productivity and performance quality. The research employed a descriptive analytical methodology, using a questionnaire as the main tool for data collection from a selected sample of employees within the organization (to be specified if applicable). The data were analyzed using the SPSS software. The results revealed a strong positive correlation between the implementation of TQM practices and improved employee efficiency. It also showed that factors like fair performance evaluation, a motivating work environment, and employee empowerment play a crucial role in enhancing employee effectiveness. The study recommends expanding the application of TQM concepts and fostering a culture of quality among employees. It emphasizes the importance of accountability and transparency in performance evaluation as key drivers in achieving organizational goals and improving overall performance.